Potent antileishmanial activity of chitosan against Iranian strain of Leishmania major (MRHO/IR/75/ER): In vitro and in vivo assay - Bahman Rahimi Esboei; Mehdi Mohebali; Parisa Mousavi; Mahdi Fakhar; Behnaz Akhoundi (Journal of Vector Borne Diseases, 2018)
Background & objectives: Leishmaniasis is one of the major neglected zoonotic parasitic diseases whose treatment and control is very complex. Pentavalent antimonials remain the primary drugs against different forms of leishmaniasis, however, resistance to antimony and its toxic effects has necessitated the development of alternative medications such as use of medicinal plants and natural compounds. The aim of the current study was to assess the in vitro and in vivo activities of chitosan as a natural resource against Leishmania major. Methods: Low molecular weight chitosan, with 95% degree of deacetylation was melted in normal saline to a final concentration of 50, 100, 200 and 400 μg/ml. Then, the promastigotes of L. major (Iranian strain) were added to the wells of 96-well plate and 20 μl of each concentration was added to the RPMI 1640 medium. Live and dead promastigotes were counted after adding 0.1% eosin stain. The efficacy of the chitosan was also examined in BALB/c mice infected with Iranian strain of L. major. All in vitro experiments were performed in triplicate and the results of in vitro and in vivo tests were compared to the acetic acid and NaOH as negative control and glucantime as positive control. Results: The low molecular weight chitosan was completely effective at concentrations of 100, 200 and 400 μg/ml on promastigotes of L. major after 180 min of application. Moreover, in the in vivo study, the mean size of dermal lesions significantly decreased in the groups treated with the chitosan compared to the control group. Interpretation & conclusion: According to the results of the study, it can be concluded that chitosan is a potent active compound against L. major and could be evaluated as a new antileishmanial drug in the future.